MTA apical plug in non-vital permanent tooth with an open apex: A case report - Dwiandhany, Wahyuni S.; Zaelan, Andi GZN. (Journal of Case Reports in Dental Medicine, 2022)
Objective: This case report discussed the treatment of an open apex using an MTA apical plug in a non-vital permanent tooth.Methode: A 39-year-old female visits the Dental Hospital of Hasanuddin University with the chief complaint of decay in her upper front tooth. The tooth was filled, and it fell out a few weeks ago. There is a history of gingival swelling a month before. Radiographic examination showed an open apex #11 with radiolucency in the apical area. Diagnosis was necrosis with a chronic apical abscess. The root canal was prepared using circumferential techniques. Then, dressing using calcium hydroxide was given. MTA was used to perform an apical plug a few weeks later.Results: Patient showed no complaints of pain, and the size of the radiolucency in the periapical area of the tooth was reduced. Following that, a post crown created on #11.Conclusion: MTA apical plugs are effective to treat non-vital permanent tooth with an open apex.